T cells and fibroblasts in affected extraocular muscles in early and late thyroid associated ophthalmopathy. Issue 5 (1st May 2000) - Pappa, Anastasia; Lawson, Joanna M M; Calder, Virginia; Fells, Peter; Lightman, Susan
Abstract : AIM: To determine whether there are differences in the lymphocytic cell infiltrate present in affected extraocular muscles (EOM) during early and late stages of thyroid associated ophthalmopathy (TAO). METHODS: 17 biopsies of affected EOMs were collected from two groups of TAO patients (n=14): the first of five patients with early, active TAO, and the second of nine patients with late, inactive TAO. The control group was of EOM biopsies taken from 14 non-TAO patients undergoing squint surgery. Immunohistochemical analysis was undertaken using the relevant monoclonal antibodies and an avidin-biotin system and the three groups compared. RESULTS: Both CD4+ and CD8+ T cells were found in the cellular infiltrate in early, active TAO specimens which were much less evident either in late, inactive stage disease or in control tissue. There was also a significant increase in both CD45RO+ and CD45RB+ cells and macrophages in early TAO compared with the others. Increased expression of HLA-DR antigen by interstitial cells including fibroblasts was detected in both early and late disease but the EOM fibres remained morphologically intact and did not express MHC class II antigens at any time. CONCLUSION: These results demonstrate that T cells are only significantly present in early disease but increased HLA-DR antigen expression on fibroblasts is observed at all stages. This suggests that T cells are much more involved in the early than the later stages of the disease process and that early activation of fibroblasts occurs. Early intervention with immunosuppressive therapy to downregulate cytokine production by T cells may significantly influence the sequelae caused by EOM fibrosis.